Analisis Spasial Faktor Sosial Ekonomi terhadap Angka Kematian Bayi di Pulau Papua - Fitrial, Nadhifan Humam; Sari, Rahma Mutiara (Politeknik Statistika STIS, 2025)
Papua Island has the highest Infant Mortality Rate (IMR) in Indonesia, with significant disparities compared to other regions. This study analyzes the influence of socioeconomic factors on IMR in 2020, using data from the 2020 Long Form Population Census with 42 districts/cities as the unit of analysis. The variables examined include women’s average years of schooling, number of health facilities, access to safe drinking water, and the open unemployment rate. The analysis revealed significant spatial autocorrelation, leading to the use of the Spatial Error Model to capture geographical interdependence affecting IMR distribution. Results show that women’s average years of schooling and access to safe drinking water have a negative effect on IMR, while the number of health facilities has a positive effect. These findings highlight the importance of incorporating spatial aspects into health policies, focusing on improving women’s education, ensuring equitable health services, and expanding access to clean water.